2017
DOI: 10.1097/pai.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Various Thresholds as Immunohistochemistry Cutoffs for Observer Agreement

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Our study shows that non-pathologists are able to generate reproducible IHC scores after appropriate training, which is in line with previous studies (17)(18)(19)40). Interestingly, intraobserver kappa values of non-pathologists in the current study were similar to those previously reported for pathologists (23,43). In general, across all three markers, disagreements were limited to one-category discordances (e.g., <10% vs. 11%-50%) for all comparisons.…”
Section: Intraobserver Agreement Of Non-pathologistssupporting
confidence: 92%
“…Our study shows that non-pathologists are able to generate reproducible IHC scores after appropriate training, which is in line with previous studies (17)(18)(19)40). Interestingly, intraobserver kappa values of non-pathologists in the current study were similar to those previously reported for pathologists (23,43). In general, across all three markers, disagreements were limited to one-category discordances (e.g., <10% vs. 11%-50%) for all comparisons.…”
Section: Intraobserver Agreement Of Non-pathologistssupporting
confidence: 92%
“…2 The immunohistochemical positivity for IDH1 was considered strong with 3+ positivity and weak with 1-2+ positivity. 5,7 All the cases have been blindly examined by an expert neuropathologist and a general pathologist together. It means that there has been no information about the final diagnosis when the IHC slides were being reviewed by the pathologist.…”
Section: Methodsmentioning
confidence: 99%
“…The slides were reviewed and the best representative block was selected for IHC with mouse monoclonal anti-R132H-IDH1 antibody (H09, Dianova, dilution 1:50, citrate-EDTA for antigen retrieval) and P53 antibody (Dako, clone DO-7, dilution 1:100, citrate-EDTA [Ethylenediamine tetraacetic acid] for antigen retrieval). Cytoplasmic positivity for IDH1 1 , 5 and nuclear positivity for P53 2 were considered positive. We considered every positive case as positive and every negative P53 as negative.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations